The New Encyclopedia of Southern Culture : Volume 24: Race - Abadie, Ann J.; Thomas, James G., Jr; Wilson, Charles Reagan; Green, Laurie B. (Laurie Beth); Holt, Thomas C. (Thomas Cleveland), 1942- (Book collections on Project MUSE., 2013)
"There is no denying that race is a critical issue in understanding the South. However, this concluding volume of The New Encyclopedia of Southern Culture challenges previous understandings, revealing the region's rich, ever-expanding diversity and providing new explorations of race relations. In 36 thematic and 29 topical essays, contributors examine such subjects as the Tuskegee Syphilis Study, Japanese American incarceration in the South, relations between African Americans and Native Americans, Chinese men adopting Mexican identities, Latino religious practices, and Vietnamese life in the region. Together the essays paint a nuanced portrait of how concepts of race in the South have influenced its history, art, politics, and culture beyond the familiar binary of black and white."--Publisher's website.